2018
DOI: 10.1063/1.5054610
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo explicitly correlated many-body Green’s function theory

Abstract: A highly scalable stochastic algorithm is proposed and implemented for computing the basis-set-incompleteness correction to the diagonal, frequency-independent self-energy of the second-order many-body Green’s function (GF2) theory within the explicitly correlated (F12) formalism. The 6-, 9-, 12-, and 15-dimensional integrals comprising the F12 correction are directly evaluated by the Monte Carlo method using appropriate weight functions for importance sampling. The method is naturally and easily parallelized,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Unlike the deterministic counterparts, they do away with the evaluation, transformation, or storage of two-electron and geminal integrals, reducing the size-dependence of cost by one to two ranks. In contrast to QMC, these methods have no bias, ECP, or Fermion sign problems (at second order at least), and can directly compute energy differences (such as correlation correction, ,, F12 correction, ,, electron binding energies, , or quasiparticle energy bands). Therefore, this method is an example of the burgeoning class of stochastic ab initio electronic structure methods. …”
Section: Introductionmentioning
confidence: 99%
“…Unlike the deterministic counterparts, they do away with the evaluation, transformation, or storage of two-electron and geminal integrals, reducing the size-dependence of cost by one to two ranks. In contrast to QMC, these methods have no bias, ECP, or Fermion sign problems (at second order at least), and can directly compute energy differences (such as correlation correction, ,, F12 correction, ,, electron binding energies, , or quasiparticle energy bands). Therefore, this method is an example of the burgeoning class of stochastic ab initio electronic structure methods. …”
Section: Introductionmentioning
confidence: 99%
“…This study along with the one reported in Ref. 59 have been conducted to lay a firm mathematical foundation of perturbation theories, 87,88 which continue to be a workhorse for efficient, converging ab initio electronic structure calculations [89][90][91][92][93][94][95][96][97][98][99][100][101] for large complex molecules and solids.…”
Section: Discussionmentioning
confidence: 99%
“…56 As shown in recent studies on both groundand excited-state properties, 57,58 similar to F12 methods, it significantly speeds up the convergence of energetics towards the CBS limit while avoiding the usage of the large auxiliary basis sets that are used in F12 methods to avoid the numerous three-and four-electron integrals. [50][51][52][53][54][59][60][61] Explicitly correlated F12 correction schemes have been derived for second-order Green function methods (GF2) 35,[62][63][64][65][66][67][68][69][70][71][72] by Ten-no and coworkers 73,74 and Valeev and coworkers. 75,76 However, to the best of our knowledge, a F12-based correction for GW has not been designed yet.…”
Section: γ(123)mentioning
confidence: 99%